Simple and Efficient Method for Tetrahydropyranylation of Alcohols and Phenols by Using Silica Supported Sodium Hydrogen Sulphate as a Catalyst - Ravi Kumar, K.; Satyanarayana, P.V.V.; Srinivasa Reddy, B. (Asian Journal of Chemistry, 2012)
A Simple and efficient process for tetrahydropyranylation of alcohols and phenols has been developed by reacting with dihydropyran at room temperature in presence of catalytic amount of silica supported sodium hydrogen sulphate.